The Role of Social Media in Marital Dissolution in Ethiopia: Impacts and Implications - Belay Sitotaw Goshu; Melaku Masresha Woldeamanueal; Anantasha Titisania Rimadewi (Budapest International Research and Critics University, 2026)
Ethiopia’s high marital dissolution rate (45% within 30 years) is exacerbated by social media’s growing influence, with 42.2 million internet users by 2023. Platforms like Facebook and WhatsApp contribute to marital conflicts, amplified by cultural and gender norms. This study investigated social media’s role in marital problems in Ethiopia, examining platforms, conflict types, cultural influences, urban-rural differences, and intervention feasibility to inform evidence-based solutions. A convergent parallel mixed-methods design was used, involving 400 survey respondents (50% male, 50% female; 200 urban, 200 rural) and 20 semi-structured interviews (10 urban, 10 rural; 50% female). Quantitative data were analyzed using SPSS (Version 27) with chi-square tests, t-tests, and logistic regression, while qualitative data underwent thematic analysis with NVivo. Social media, particularly Facebook and WhatsApp, drives 68% of reported marital conflicts, including jealousy (51%), infidelity suspicions (37%), and communication breakdowns (32%). Urban couples face higher conflict prevalence (75%) than rural ones (61%) due to greater platform access. Patriarchal and collectivist norms amplify conflicts, with women reporting more jealousy. Digital literacy (M=4.12) and counseling (M=3.98) were rated highly effective interventions. Social media significantly undermines marital stability in Ethiopia, with urban areas and women most affected. Cultural norms exacerbate conflicts, but digital literacy and counseling offer viable mitigation strategies. Implement urban-focused digital literacy programs, gender-sensitive counseling, and community-based workshops, supported by enhanced content moderation in local languages.